Immune microenvironment-dependent effects of age-associated Bifidobacterium strains on gut immunity and microbial diversity - He, Yaqin; Zhang, Furui; Tian, Zhiqiang; Li, Ruyi; Su, Ming; Hong, Liping; Wen, Jun; Zhang, Cao; Tian, Jinhai; Guo, Le (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe applications of probiotics in food and infant formula are greatly increased. Bifidobacterium, a genus of beneficial bacteria, plays a crucial role in the human gut microbiota. Despite extensive research on probiotics, how age-associated Bifidobacteria strains modulate gut immunity and microbial diversity remains unclear.MethodsOur present study investigates the immunomodulatory effects of two Bifidobacterium strains, Bifidobacterium adolescentis (BA) and Bifidobacterium longum subsp. infantis (BI), on gut immunity and microbial diversity using three models: a DSS-induced chronic colitis mouse model, germ-free mouse model, and in vitro human intestinal γδ T cell co-culture system.ResultsTranscriptomic analysis in the DSS-induced colitis model revealed differential gene expression, particularly in cytokine signaling pathways and γ-chain-related cytokines crucial for γδ T cell function. Both BA and BI reduced γδ T cell infiltration in colorectal tissues, and modulated immune activation markers, with distinct effects on peripheral blood γδ T cell levels. RNA-seq analysis post-probiotic treatment highlighted strain-specific changes, with BA activating NOD2-like receptor signaling and BI enhancing IL-17 and TNF signaling pathways. Direct co-culture experiments demonstrated BI's robust activation of γδ T cells, while BA showed minimal direct effects. Multi-omics correlation analysis suggested that BA and BI modulated immune responses through microenvironment-dependent mechanisms, offering potential therapeutic insights for gut-related inflammatory diseases.ConclusionsOur findings provide a theoretical basis for the development of age-associated probiotic intervention strategies, offering new insights into personalized microbiota modulation to enhance immune health and gut homeostasis across different life stages.